PENGEMBANGAN GAMELAN JEGOG SEBAGAI DAYA TARIK WISATA DI KABUPATEN JEMBRANA - Edy Wirawan, I Komang; Sutjiati Beratha, Ni Luh (Jurnal Master Pariwisata (JUMPA); Volume 03, Nomor 01, Juli 2016, 2016)
Jembrana have a number of cultural potentials that can be developed as tourist attractions, one of which is the art of gamelan jegog musical instrument. Gamelan jegog made of bamboo and produce a beautiful tone. This study aims to identify the potential and constraints gamelan jegog as a tourist attraction, and to formulate an effective development strategy to be implemented. Data collection techniques used in this study were the observation, structured interviews with 11 informants from the community and the government that has insights of gamelan jegog. The method used is descriptive-qualitative and SWOT analysis. The results showed that the gamelan jegog potential can be developed into a tourist attraction in Jembrana by minimizing the constraints owned. Through SWOT approach then obtained jegog gamelan development strategy in the form of SO (strength-opportunities) strategy, namely the development of tourism potential in the district of Jembrana and increase cooperation and utilization of technology.
Keywords: Development, Tourist Attractions, Gamelan Jegog